Makna Interaksi Guru–Anak dalam Pembentukan Karakter Prososial dan Moral-Religius Anak Usia Dini: Studi Fenomenologi di TK Lab School FIP UMJ - Imam Mujtaba; Yoga Aditia Ragil (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2026)
This study aims to analyze the meaning and practice of teacher-child interactions in shaping prosocial and moral-religious character in early childhood education. The study uses a qualitative approach with a phenomenological design to understand the subjective experiences of teachers in building children's character through daily interactions. The research subjects consisted of four teachers at the Lab School FIP UMJ kindergarten. Data were collected through classroom observation, in-depth interviews, and documentation studies, then analyzed using data reduction techniques, open coding, thematic categorization, and essential meaning extraction. The results showed that teacher-child interactions were interpreted as a dialogical, reflective, and exemplary relational process. The practice of interaction in shaping prosocial character was manifested through conflict mediation, sharing habits, positive reinforcement, and empathy development. Meanwhile, moral-religious character building is carried out through the habit of worship, the use of polite language, behavioral reflection, and the internalization of values through the real example of teachers. The challenges faced include differences in family backgrounds, consistency in habits, and the dynamics of children's emotional regulation. This study confirms that the quality of teacher-child interaction is a strategic foundation in ensuring the quality of character education in early childhood education.